2018
DOI: 10.2217/fca-2017-0072
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Stem Cells in Cardiac Repair

Abstract: One out of every two men and one out of every three women greater than the age of 40 will experience an acute myocardial infarction (AMI) at some time during their lifetime. As more patients survive their AMIs, the incidence of congestive heart failure (CHF) is increasing. 6 million people in the USA have ischemic cardiomyopathies and CHF. The search for new and innovative treatments for patients with AMI and CHF has led to investigations and use of human embryonic stem cells, cardiac stem/progenitor cells, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“…Additionally, c-kit + stem cells in bone marrow could be mobilized after acute MI. 30 The proportion of c-kit + cells in infarcted areas is gradually increased. 31 Studies have shown that the homing of c-kit + stem cells to infarct sites undoubtedly has significance with respect to the improvement of cardiac function and repair, although these cells cannot differentiate into cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, c-kit + stem cells in bone marrow could be mobilized after acute MI. 30 The proportion of c-kit + cells in infarcted areas is gradually increased. 31 Studies have shown that the homing of c-kit + stem cells to infarct sites undoubtedly has significance with respect to the improvement of cardiac function and repair, although these cells cannot differentiate into cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Les CSMO dans le cadre d'ECV sont capables de régénérerl ec oe ur par 3m é canismes différents : La différenciation en cellules cardiaques une fois mobilisées ; La stimulation de la prolifération et de la différenciation des cellules souches cardiaques résidentes et la repopulation des CS résidentes pour maintenir l'homéostasie du tissu ; La sécrétion de facteurs paracrines permettant de réduire l'apoptose des cellules cardiaques, d'activer la différenciation des cellules souches résidentes et la formation de nouveaux vaisseaux sanguins tout en diminuant les processus inflammatoires et fibrotiques [24]. L'efficacité de l'injection de CSMO après un infarctus du myocarde a été observéed ans plusieurs études [45]. Les principaux bénéfices rapportéss ont une diminution de la taille de l'infarctus, une amélioration de la perfusion cardiaque, de la contractibilité,d el 'ESV (End Systolic Volume) et de la FEVG (Fraction d'Ejection du Ventricule Gauche) par rapport au groupe contrôle [46][47][48].…”
Section: Maladies Cardiovasculaires (Mcv)unclassified
“…Stem cells secrete high amounts of paracrine factors that can stimulate endogenous repair mechanisms ( Henning, 2018 ). Human embryonic stem cell-derived cardiomyocytes repair the macaque monkey hearts by reducing scar tissue and improving cardiac functionality ( Liu et al, 2018 ).…”
Section: Resolving But Not Dampening Inflammation For Cardiac Healingmentioning
confidence: 99%